Integrasi materi dasar teknik arsitektur dalam pembentukan pemahaman desain arsitektur pada mahasiswa semester awal - 'Aini, Nurma Nur (Maliki Interdisciplinary Journal, 2026)
In the first semester of the Architectural Engineering study program, discussions are very important in shaping the mindset, so that it can provide a basic understanding and design skills of students. Courses such as Basic Construction, Basic Aesthetics, and Introduction to Architecture are the main foundation in this process. This article provides a discussion related to and integration of these materials in building the understanding of architectural engineering students, especially in the context of learning at UIN Maulana Malik Ibrahim Malang. In all discussions it shows that the understanding of construction elements such as foundations, beams, columns, and roofs requires a journey that is in harmony with the mastery of the aesthetic aspects of two dimensions, color, nirmana, and 3D composition of nature. In addition, the concept of transformation in the introduction to architecture and the value of Rahmatan lil Alamin play a role in providing insight into how to form designs that are not only functional and aesthetic but also have humanitarian and sustainable values. In this study, it is hoped to provide an overview of the importance of integrating basic materials.